Valor razonable versus coste histórico de los activos biológicos: valor predictivo de la información contable: Fair value versus historical cost-based valuation for biological assets: predictability of financial information - Argilés-Bosch, Josep M.; Garcia-Blandon, Josep; Monllau, Teresa (Revista de Contabilidad - Spanish Accounting Review, 2011)
There is an intense debate on the convenience of moving from historical cost (HC) toward the fair value (FV) principle. The debate and academic research is usually concerned with financial instruments, but the IAS 41 requirement of fair valuation for biological assets brings it into the agricultural domain. This paper performs an empirical study with a sample of Spanish farms valuing biological assets at HC and a sample applying FV, finding no significant differences between both valuation methods to assess future cash flows. However, most tests reveal more predictive power of future earnings under fair valuation of biological assets, which is not explained by differences in volatility of earnings and profitability. The study also evidences the existence of flawed HC accounting practices for biological assets in agriculture, which suggests scarce information content of this valuation method in the predominant small business units existing in the agricultural sector in advanced Western countries.